Optimal pest control problem in population dynamics - Rafikov, Marat; Balthazar, Jose Manoel [UNESP] (Springer, 2005)
One of the main goals of the pest control is to maintain the density of the pest population in the equilibrium level below economic damages. For reaching this goal, the optimal pest control problem was divided in two parts. In the first part, the two optimal control functions were considered. These functions move the ecosystem pest - natural enemy at an equilibrium state below the economic injury level. In the second part, the one optimal control function stabilizes the ecosystem in this level, minimizing the functional that characterizes quadratic deviations of this level. The first problem was resolved through the application of the Maximum Principle of Pontryagin. The Dynamic Programming was used for the resolution of the second optimal pest control problem.
Keywords: optimal pest control; Maximum Principle of Pontryagin; Hamilton-Jacobi-Bellman equation